Development of a novel inducer for EBV lytic therapy. Issue 16 (15th August 2019) - Tikhmyanova, Nadezhda; Paparoidamis, Nicholas; Romero-Masters, James; Feng, Xin; Mohammed, Farheen Sultana; Reddy, Poli Adi Narayana; Kenney, Shannon C.; Lieberman, Paul M.; Salvino, Joseph M.
Graphical abstract: Preliminary SAR studies and in vivo reactivation of EBV in SNU719 gastric carcinoma and AGS-Akata gastric carcinoma xenograft mouse model. Abstract: Epstein-Barr virus (EBV) is a human herpesvirus that infects over 90% of the world's population that persists as a latent infection in various lymphoid and epithelial malignancies. The total number of EBV associated malignancies is estimated to exceed 200, 000 new cancers per year. Current chemotherapeutic treatments of EBV-positive cancers include broad-spectrum cytotoxic drugs that ignore the EBV positive status of tumors and have limited safety and selectivity. In an effort to develop new and more efficacious molecules for inducing EBV reactivation, we have developed high-throughput screening assays to identify a class of small molecules (referred to as the C60 series) that efficiently activate the EBV lytic cycle in multiple latency types, including lymphoblastoid and nasopharyngeal carcinoma cell lines. In this paper we report our preliminary structure activity relationship studies and demonstrate reactivation of EBV in the SNU719 gastric carcinoma mouse model and the AGS-Akata gastric carcinoma mouse model.